Leukemia Gene Atlas – A Public Platform for Integrative Exploration of Genome-Wide Molecular Data - Hebestreit, Katja; Gröttrup, Sören; Emden, Daniel; Veerkamp, Jannis; Ruckert, Christian; Klein, Hans-Ulrich; Müller-Tidow, Carsten; Dugas, Martin (PLOS ONE, 2012)
Leukemias are exceptionally well studied at the molecular level and a wealth of high-throughput data has been published. But further utilization of these data by researchers is severely hampered by the lack of accessible integrative tools for viewing and analysis. We developed the Leukemia Gene Atlas (LGA) as a public platform designed to support research and analysis of diverse genomic data published in the field of leukemia. With respect to leukemia research, the LGA is a unique resource with comprehensive search and browse functions. It provides extensive analysis and visualization tools for various types of molecular data. Currently, its database contains data from more than 5,800 leukemia and hematopoiesis samples generated by microarray gene expression, DNA methylation, SNP and next generation sequencing analyses. The LGA allows easy retrieval of large published data sets and thus helps to avoid redundant investigations. It is accessible at www.leukemia-gene-atlas.org.